Development of AstroMotion Media to Improve Students' Critical Thinking Skills in Natural Science Learning - Utami, Anggi Putri; Rambe, Andina Halimsyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to develop AstroMotion media that are valid, practical, and effective in improving students' critical thinking skills in Natural Science learning. The method used in this study was Research and Development (R&D) employing the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 24 sixth-grade students at MIS Al-Barkah. The research instruments included validation questionnaires, practicality questionnaires, as well as pre-test and post-test questions. The validation results show that the media is rated as very valid by media experts based on physical aspects, usability, illustrations, color, and images, with a score of 89.4%, and by material experts with a score of 90%. The practicality of the media, based on student responses, is 88.43%, and from the teacher, it is 90%, both categorized as very practical. Data analysis using the N-gain formula shows an increase in the average score from 57.7 to 87.7, with an N-gain score of 0.71, which is classified in the high category. Therefore, AstroMotion media is proven to be effective and suitable for use as a learning tool in Natural Science to improve students’ critical thinking skills